Associations between cultural characteristics and antibacterial activities of Streptomyces isolates: a preliminary analysis - Tasrip, Nor Asmara; Mohd Desa, Mohd Nasir; Cheah, Yoke Kqueen; Chong, Pei Pei; Shamsudin, Mariana Nor (2012)
40 Streptomyces isolates were recovered from soils taken from various sites around Universiti Putra Malaysia (UPM) and nearby peripheral areas, including 4 from a far-off location. Identification was done by conventional and molecular approaches (16S rRNA and rpoB genes sequence homology). All isolates were subjected to antibacterial assay against 2 pathogenic bacteria of gram positive and gram negative (Escherichia coli ATCC 25922 & Staphylococcus aureus ATCC 25923), by perpendicular streak method using MHA and TSA as the test media. With MHA as the test media in the antibacterial assay, > 50 % of the isolates showed antibacterial activity to at least one of the test bacteria as compared by using TSA as the test media. Color series of aerial mycelium was described based on growth on ISP-2 medium; there was a significant association between grey and non-grey color series of the aerial mycelium in association with the antibacterial activity of the isolates on MHA (89% vs. 42% respectively, P = 0.013) and TSA (78% vs. 35% respectively, P = 0.025). As a conclusion, different chemical composition of the test media could have an effect on the outcome of the antibacterial assay (MHA vs. TSA). The observed relationship between aerial mass-color (grey vs. nongrey) and antibacterial activity warrant further investigation in a larger sample of isolates.